1989
DOI: 10.1128/mcb.9.6.2370
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface and Golgi pools of beta-1,4-galactosyltransferase are differentially regulated during embryonal carcinoma cell differentiation.

Abstract: beta-1,4-Galactosyltransferase (GalTase) has two functionally distinct subcellular distributions. In the Golgi apparatus, GalTase participates in the glycosylation of secretory and membrane-bound glycoproteins, whereas on the cell surface it mediates specific aspects of intercellular adhesion. For this study, a murine GalTase clone was obtained by screening a lambda gt10 cDNA library made from F9 embryonal carcinoma cells with a heterologous bovine GalTase cDNA probe. The murine GalTase cDNA probe was used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 29 publications
2
28
2
Order By: Relevance
“…5). These results are similar to those reported in F9 cells with ,B-1,4-galactosyltransferase (29) and suggest that the dynamic changes in cell surface oligosaccharide structures known to accompany in vitro differentiation of this cell line (10) are associated with significant changes in glycosyltransferase gene expression.…”
Section: I T M L Q D L H V N K I S M S R S K S E T S L P S S R S G supporting
confidence: 79%
“…5). These results are similar to those reported in F9 cells with ,B-1,4-galactosyltransferase (29) and suggest that the dynamic changes in cell surface oligosaccharide structures known to accompany in vitro differentiation of this cell line (10) are associated with significant changes in glycosyltransferase gene expression.…”
Section: I T M L Q D L H V N K I S M S R S K S E T S L P S S R S G supporting
confidence: 79%
“…It has been reported that ␤1,4GT activity decreases to approximately one-third of control values during the first 3 days of differentiation of F9 cells following RA addition and then begins to rise slowly on day 4 following RA treatment (53). Consistent with this, we found that the activity of the ␤1,4GT in extracts of both F9 and RA/F9 cells is similar during the first 3 days following RA treatment (data not shown).…”
Section: Time Course Of Induction Of ␣13gt Enzyme Activity In F9 Celsupporting
confidence: 78%
“…However, using a different assay for fucosyltransferase activity another group observed a slight increase in the activity of fucosyltransferase upon RA treatment of F9 cells (88). In the case of ␤1,4GT, it was shown that ␤1,4GT activity in F9 cells declines after 3 days of differentiation and then begins to rise around 5-6 days of differentiation, which correlates with increased levels of transcript observed after 5-6 days of treatment with RA (53). Recently, it was reported that neither the ␤1,4GT enzyme nor transcript levels change significantly in F9 cells treated with RA alone, but treatment with RA and cAMP causes a 6.5-fold induction of the transcript in 8 days (54).…”
Section: Discussionmentioning
confidence: 87%
“…The level of GalT I on the cell surface is differentially regulated from that in the Golgi pool and is not the result of simple bulk flow of Golgi-derived vesicles to the cell surface (Lopez et al, 1989). This suggests that the Golgi and surface pools of GalT I result from distinct protein species and/or molecular pathways (reviewed by Shur et al, 1998).…”
mentioning
confidence: 99%